The prion protein family: a view from the placenta - Makzhami, Samira; Passet, Bruno; Halliez, Sophie; Castille, Johan; Moazami-Goudarzi, Katayoun; Duchesne, Amandine; Vilotte, Marthe; Laude, Hubert; Mouillet-Richard, Sophie; Béringue, Vincent; Vaiman, Daniel; Vilotte, Jean-Luc (Frontiers in Cell and Developmental Biology, 2014)
Based on its developmental pattern of expression, early studies suggested the implication of the mammalian Prion protein PrP, a GPI-anchored ubiquitously expressed and evolutionary conserved glycoprotein encoded by the Prnp gene, in early embryogenesis. However, gene invalidation in several species did not result in obvious developmental abnormalities and it was only recently that it was associated in mice with intra-uterine growth retardation and placental dysfunction. A proposed explanation for this lack of easily detectable developmental-related phenotype is the existence in the genome of one or more gene (s) able to compensate for the absence of PrP. Indeed, two other members of the Prnp gene family have been recently described, Doppel and Shadoo, and the consequences of their invalidation alongside that of PrP tested in mice. No embryonic defect was observed in mice depleted for Doppel and PrP. Interestingly, the co-invalidation of PrP and Shadoo in two independent studies led to apparently conflicting observations, with no apparent consequences in one report and the observation of a developmental defect of the ectoplacental cone that leads to early embryonic lethality in the other. This short review aims at summarizing these recent, apparently conflicting data highlighting the related biological questions and associated implications in terms of animal and human health.